2020
DOI: 10.5606/tgkdc.dergisi.2020.18905
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of edaravone in acute limb ischemia/reperfusion injury

Abstract: Akut alt ekstremite iskemi-reperfüzyon hasarında edaravonun renal koruyucu etkisi ÖZ Amaç: Bu deneysel çalışmada, sıçan modelinde akut alt ekstremite iskemi/reperfüzyonuna bağlı böbrek hasarında edaravonun etkinliği araştırıldı. Ça lış ma pla nı: Bu çalışmada Haziran 2015-Ağustos 2015 tarihleri arasında toplam 40 erkek Wistar sıçan kullanıldı. Sıçanlar sham, iskemi/reperfüzyon, edaravon ve solvent gruplarına randomize edildi (n=10 her bir grupta). İnfrarenal abdominal aort 120 dk. süreyle klemlendi ve sonrasın… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The reactive oxygen species (ROS), which can cause direct damage to lipids in cell membranes and also to the intracellular structures such as nucleic acids and mitochondria, are the major mediators of these harmful effects. [ 1 ] The ROS can induce the production of proinflammatory cytokines that trigger acute tissue inflammation and injury in the ischemic and remote organs through activating various molecules, including the intracellular signaling molecule nuclear factor kappa beta (NF-kB). [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…The reactive oxygen species (ROS), which can cause direct damage to lipids in cell membranes and also to the intracellular structures such as nucleic acids and mitochondria, are the major mediators of these harmful effects. [ 1 ] The ROS can induce the production of proinflammatory cytokines that trigger acute tissue inflammation and injury in the ischemic and remote organs through activating various molecules, including the intracellular signaling molecule nuclear factor kappa beta (NF-kB). [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…In practical terms, there would be no reason to deploy tourniquets in the absence of active hemorrhage. However, conventional murine models in the literature were produced with application of tourniquets without hemorrhage (Klausner et al, 1989;Adachi et al, 2006;Hsu et al, 2012;Yang et al, 2012;Mansour et al, 2014;Kao et al, 2015a;Kao et al, 2015b;Karahan et al, 2016;Onody et al, 2016;Foster et al, 2017;Shih et al, 2018;İnce et al, 2019;Packialakshmi et al, 2022). We describe a new TILLIR injury model, which was produced by first inducing hemorrhage then applying tourniquets.…”
Section: Discussionmentioning
confidence: 98%
“…Although pigs are more similar to humans in physical size, physiology and immunology than rodents (Packialakshmi et al, 2020;Zhou, 2022), rodents are easy to handle, quickly reproduce and have contributed significantly to deciphering pathophysiology and developing novel therapies. As such, a majority of tourniquet-induced lower limb ischemia/ reperfusion (TILLIR) injury in the literature has been produced in rodents, and a variety of therapies have been tested using rodent models (Klausner et al, 1989;Adachi et al, 2006;Hsu et al, 2012;Mansour et al, 2014;Kao et al, 2015a;Kao et al, 2015b;Karahan et al, 2016;Onody et al, 2016;Foster et al, 2017;Shih et al, 2018;İnce et al, 2019).…”
Section: Figurementioning
confidence: 99%
“…According to the MRI results before and after treatment, the tissue bleeding caused by ischemia-reperfusion injury in the two groups has improved, but the observation group is significantly better than the control group. A large number of studies have shown that edaravone can directly scavenge hydroxyl radicals through electrons and inhibit the chain reaction of cell membrane peroxidation, thereby effectively reducing the damage of intracellular oxygen free radicals [5,17], to indirectly alleviate the bleeding caused by vascular endothelial cell injury. is study also analyzed the two groups of patients before and after treatment of serum SOD, MDA levels, and Bcl-2, Bax, and Caspase-3 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Edaravone is a free radical scavenger, which is first used in the treatment of cerebral ischemia-reperfusion injury. The long-term clinical practice has proved that edaravone has a significant effect on the treatment of ischemic reperfusion injury [ 5 , 6 ]. Mailuoning, as a traditional Chinese medicine preparation with antithrombotic and blood viscosity reduction, has a protective effect on limb ischemia-reperfusion injury, but there is a lack of research on the therapeutic effect between it and edaravone.…”
Section: Introductionmentioning
confidence: 99%